Determinants of Credit Disbursement in Small Indonesian Commercial Banks: An ARDL Cointegration Analysis - Safri Adriansyah; Farah Wulandari Pangestuty (Priviet Social Sciences Journal, 2026)
This study investigates the determinants of credit disbursement in small commercial banks in Indonesia, highlighting their essential role in economic growth. It focuses on banks with core capital below IDR 6 trillion and examines key variables such as credit interest rates, inflation, exchange rates, and shadow banking. Despite theoretical expectations of proportional credit growth across banks, a paradox emerges: while large banks show an upward trend in credit disbursement, small banks face stagnation or decline. Unlike previous research, this study incorporates shadow banking as a determinant, offering a more comprehensive perspective on the macroeconomic, microeconomic, and institutional factors influencing credit distribution. To analyze these relationships, the study employs the Autoregressive Distributed Lag (ARDL) approach, which captures both short- and long-term effects while addressing variations in data stationarity. The findings reveal that most variables significantly impact long-term credit disbursement, whereas short-term effects differ across variables. This underscores the complex operational landscape of small banks. Notably, shadow banking exerts a substantial influence in both the short and long run, further shaping credit dynamics. Based on these insights, the study recommends that small banks diversify their services and strengthen strategic collaborations to enhance credit accessibility and financial stability.